Some Analytical Consideration on Indonesian Metal Music - Gianluca Cellini (IJCAS (International Journal of Creative and Arts Studies), 2017)
The widespread of metal music had crossed the borders of its native lands as a musical and socio-cultural phenomenon that emerged many studies mostly starting from sociological standpoint. By emphasizing the musicological aspect, this paper tried to show how the theoretical proposals of some scholars may be reflected in particular metal music through structural analysis approach. The analysis of a particular folk metal music in Indonesia showed the inclination of its instruments to mimic the interlocking of Balinese Gamelan in terms of patterns, hierarchy, and scale. The character of folk metal music in Indonesia was explained as the rebellion against a world unrestrained consumerism yet in the same time was an attempt to follow the post-modern need to find meeting points that is practicable. This paper suggested to insert the phenomenon of Indonesian metal music in the broader framework of worldwide expansion of this genre.